Performance Analysis of IoT-Based pH and EC Control System for Smart Indoor Hydroponics Pagoda Mustard Cultivation - Bagus Muhammad Akbar; Shoffan Saifullah; Arif Umami (Politeknik Negeri Cilacap, 2026)
Indoor hydroponic systems increasingly utilize IoT technologies for automated nutrient management, yet empirical performance data from extended operational trials remain scarce. This study quantifies control system performance and biological validation for an IoT-based pH-EC control implementation during 35-day continuous operation. The system employed ESP32 microcontroller with safety-based threshold control (pH <8.2, TDS >900 ppm) optimized for reliability rather than precision in a 30L Deep Flow Technique system cultivating 14 pagoda mustard plants. Analysis of 12,219 datapoints revealed TDS control achieved 99.3% time-in-safe-range (MAE 50.06 ppm, settling time 671.6 min) while pH control maintained MAE 0.74 units (settling time 1266.9 min) without exceeding critical thresholds. Plant outcomes validated control effectiveness: final height 20.59 ± 2.03 cm, leaf count 35.50 ± 11.83, with consistent SPAD values >40 indicating adequate nitrogen nutrition despite sub-optimal TDS levels (867 ppm vs. optimal 1050-1400 ppm). Results demonstrate that simplified rule-based control achieves satisfactory biological outcomes when safety thresholds prevent metabolic stress, contributing validated operational benchmarks for resource-constrained hydroponic applications.